Novel quantitative assessment system of liver steatosis using a newly developed attenuation measurement method. Issue 10 (18th May 2018) - Tamaki, Nobuharu; Koizumi, Yohei; Hirooka, Masashi; Yada, Norihisa; Takada, Hitomi; Nakashima, Osamu; Kudo, Masatoshi; Hiasa, Yoichi; Izumi, Namiki
Abstract : Aim: The present study has developed and evaluated the effectiveness of a new echo attenuation measurement function combined with an ultrasonic diagnostic system for the accurate diagnosis of liver steatosis. Methods: A multicenter prospective study involving patients with chronic hepatitis was carried out. All patients underwent liver biopsy, and attenuation coefficient (ATT) was measured on the same day. The fat area (%) of biopsy specimens was quantitatively evaluated. Correlations between ATT, steatosis grade, and fat area were evaluated. Results: A total of 351 patients were enrolled in this study. The median values of fat area for steatosis grades S0, S1, S2, and S3 were 0.6%, 3.2%, 6.4%, and 15.5%, respectively. A significant correlation was found between fat area and steatosis grade ( P  < 0.001). Similarly, the median values of ATT for steatosis grades S0, S1, S2, and S3 were 0.55, 0.63, 0.69, and 0.85 dB/cm/MHz, respectively, and ATT increased with an increase in the steatosis grade ( P  < 0.001). Attenuation coefficient was significantly correlated with fat area (r = 0.50, P  < 0.001). The area under the receiver operating characteristic curve corresponding to S ≥ 1, S ≥ 2, and S ≥ 3 were 0.79, 0.87, and 0.96, respectively. Similarly, the sensitivity and specificity of S ≥ 1, S ≥ 2, and S ≥ 3 were 72%, 82%, and 87% and 72%, 82%, and 89%, respectively. Conclusions: The newly developed ATT measurement for evaluation of liver steatosis was closely correlated with steatosis grade and automated quantification of fat area, and it provides clinically relevant information.